Implementation of the RBQ Plus Program in Improving Qur'anic Literacy of Bogem Village Residents, Gurah, Kediri - Guntur Febri Tinanto; Bagus Jamroji (PT. Caesarindo Triloka Persada, 2026)
Qur’anic literacy constitutes a fundamental component of Islamic education, playing a crucial role in shaping religious understanding and moral character. However, Qur’anic literacy among rural communities remains suboptimal, necessitating the development of sustainable, community-based non-formal Islamic education models. This study aims to analyze the implementation of the RBQ Plus Program (Rumah Belajar Qur’an Plus) in enhancing Qur’anic literacy among residents of Bogem Village, Gurah District, Kediri Regency, and to identify supporting and inhibiting factors as well as its impact on the internalization of Qur’anic values. This research employs a qualitative approach with a descriptive phenomenological design. Data were collected through observation, in-depth interviews, and documentation involving program managers, Qur’an instructors, parents, and learners. Data analysis followed the Miles and Huberman interactive model, with triangulation applied to ensure data credibility. The findings reveal that the RBQ Plus Program is implemented systematically through Qur’anic reading instruction, habitual recitation (tilawah), reinforcement of verse comprehension, and the integration of Islamic educational values into daily life. Supporting factors include learners’ motivation, educator competence, and strong family and community support, while limited facilities and heterogeneous participant backgrounds emerge as inhibiting factors. The program contributes significantly to improving tajwid-based reading skills, enhancing basic Qur’anic understanding, and strengthening religious character among community members.